Swiss Public Administration Making the State Work Successfully - Ladner, Andreas; Soguel, Nils; Emery, Yves; Weerts, Sophie; Nahrath, Stéphane (Governance and Public Management, 2019)
Swiss citizens approve of their government and the way democracy is practiced; they trust the authorities and are satisfied with the range of services Swiss governments provide. This is quite unusual when compared to other countries. This open access book provides insight into the organization and the functioning of the Swiss state. It claims that, beyond politics, institutions and public administration, there are other factors which make a country successful. The authors argue that Switzerland is an interesting case, from a theoretical, scientific and a more practice-oriented perspective. While confronted with the same challenges as other countries, Switzerland offers different solutions, some of which work astonishingly well.